Computational modeling of an oscillating water column device for the Rio Grande coast - Gomes, Mateus das Neves (2010)
This work presents the computational modeling of a converter of wave energy in electrical energy. The converter is Oscillating Water Column (OWC) type, submitted to the wave climate of Rio Grande city. The numerical simulation was performed using FLUENT® package and employing the multiphase Volume of Fluid (VOF) model in the wave generation and in the interaction between the wave and the converter device. The computational domain was represented by a wave tank coupled with the OWC device. This domain allows the behavior analysis to be performed when the device is subjected to the incidence of regular waves. The waves were molded to represent the characteristics of the Rio Grande coast climate. Results demonstrate that the OWC converter can be successfully used to convert the Rio Grande's coast wave energy in useful electrical energy.